Building a Sustainable Quality MattersTM Community of Practice Through Social Network Analysis. Issue 3 (3rd July 2017) - Cowan, John; Richter, Stephanie; Miller, Tracy; Rhode, Jason; Click, Aline; Underwood, Jason
ABSTRACT: The growth of distance education has necessitated strong evidence of quality for institutions of higher education, and numerous standards and principles of quality have been developed, such as Quality Matters™ (Quality Matters). These systems are often considered only at the course level to guide design and improve student outcomes, but they can also help to pull the institution together and galvanize advancement in online development. Adopting online quality standards can be a complex process that requires changes to institutional culture. This article describes how the use of the Community of Practice (CoP) framework engaged a campus-wide network of individuals in adoption of the Quality Matters training, rubric, and review process to advance distance education support and online course development. Using Social Network Analysis, researchers were able to identify the strengths and weakness of the CoP during the early adoption phase of Quality Matters to quantitatively measure the connections among members of the community. Based on a survey administered to every participant who attended the Applying the Quality Matters Rubric™ (APPQMR) workshop, researchers analyzed connections across the Quality Matters™ (Quality Matters) Community of Practice (CoP). This analysis indicated strong cohesion of the network based on work related to distance education but low density for connections based on Quality Matters. Furthermore, it demonstrated that significant connections existed between members prior to the adoption of Quality Matters and identified key influencers within the network. The results also indicated that the Quality Matters leadership team at the institution is highly central to the Quality Matters CoP network. The results can be used to identify strategies to further adoption of Quality Matters at the institution by strengthening the CoP.